The Discussion of Ulama and Ideology in The Indonesian Ideological Decade - Arditya Prayogi; Noorma Fitriana M. Zain; Devy Arisandi (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
The ideological decade in Indonesia was marked by the entry of various transnational ideologies. Thus, these various ideologies will be responded to with various responses that are different from each other, including the responses of the ulama as representatives of Indonesian Muslims (still the Dutch East Indies at that time). This article aims to describe various forms of response to several ideologies that developed during the ideological decade and their discourses. This article was written with a qualitative descriptive approach using the literature study method as the data collection method. From the results of the analysis, it can be concluded that the ulama as well as Muslims are fragmented in various responses and the roles shown in their various attitudes, when responding to the entry of various ideas/ideologies at this time. In the life of the community, the estuary of the responses that appear leads to the pros and cons of these ideas/ideologies.